Psychometric Properties of the Brief Resilience Scale in Honduran University Students - Hidalgo-Fuentes, Sergio; Martínez Álvarez, Isabel; Llamas-Salguero, Fátima; Pineda-Zelaya, Iris Suyapa (Anales de Psicología / Annals of Psychology, 2026)
University students face challenges that can generate high levels of stress, which may have negative consequences for both their health and academic performance. However, resilience plays a key role in students’ ability to cope with and overcome the difficulties of this educational stage. One of the most commonly used tools to assess resilience is the Brief Resilience Scale (BRS). The present study investigated the psychometric properties of the BRS in a sample of Honduran university students. The sample included 791 students (Mage = 26.29 years, SD = 8.02). The reliability, construct validity, as well as concurrent and divergent validity of the BRS were evaluated. Additionally, measurement invariance by sex and floor and ceiling effects were analyzed. Exploratory and confirmatory factor analyses supported the two-factor structure of the BRS, and the results showed acceptable reliability indices. Measurement invariance was observed between men and women. This study provides preliminary evidence that the Spanish version of the BRS is a reliable and valid instrument for assessing resilience in university students in Honduras.